Slide11.JPG

Slide12.JPG

Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class


Transcript

Example 5 Find the roots of the quadratic equation 3x2 − 2 √6 𝑥 + 2 = 0 . 3x2 – 2 √6 𝑥+2=0 We will factorize using splitting the middle term method 3x2 – √𝟔 𝒙−√𝟔 𝒙+𝟐=𝟎 3x2 – √(2×3) 𝑥−√(2×3) 𝑥+2=0 3x2 – (√2)(√3)𝑥−(√2)(√3)𝑥+2=0 √3 𝑥(√3 𝑥−√2 )−√2 (√3 𝑥−√2 )=0 (√𝟑 𝒙 −√𝟐) (√𝟑 𝒙−√𝟐)=𝟎 √3 𝑥 −√2 = 0 √3 𝑥 = √2 x = √𝟐/√𝟑 = √(𝟐/𝟑) √3 𝑥 −√2 = 0 √3 𝑥 = √2 x = √𝟐/√𝟑 = √(𝟐/𝟑) Hence, x =√(𝟐/𝟑) & x =√(𝟐/𝟑) are roots of the equation

Ask a doubt
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 13 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.